2011
DOI: 10.1177/1053451210395386
|View full text |Cite
|
Sign up to set email alerts
|

Point Systems Made Simple With Google Docs

Abstract: Using a typical point system, student behavior is evaluated at regular intervals, and students receive points based on demonstration of desired behavior. Points can then be used to buy preferred activities or items. In most cases, the classroom teacher keeps track of points earned/spent using some sort of paper filing system or notebook. This article presents how Google Docs can be utilized to improve and simplify the management of classwide point systems. Google DocsGoogle Docs is a web-based document, spread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…In parallel, since the LTSI is a property of Bates and colleagues and was made for commercial purpose, we had to secure an authorization to use the instrument for academic research. Fortunately, Bates et al () already had a version of the LTSI in Thai and even proposed to us another translated version, for instance in Mandarin. We compared Yamnill and Mclean’s () LTSI translation in the Thai language with Bates’s translated version and found some differences which were explained by the fact that Yamnill and Mclean () used an old version of the LTSI that is version 2 which was recently updated to version 4.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In parallel, since the LTSI is a property of Bates and colleagues and was made for commercial purpose, we had to secure an authorization to use the instrument for academic research. Fortunately, Bates et al () already had a version of the LTSI in Thai and even proposed to us another translated version, for instance in Mandarin. We compared Yamnill and Mclean’s () LTSI translation in the Thai language with Bates’s translated version and found some differences which were explained by the fact that Yamnill and Mclean () used an old version of the LTSI that is version 2 which was recently updated to version 4.…”
Section: Methodsmentioning
confidence: 99%
“…Bates et al () LTSI scale was used to assess the respondents’ learner characteristics and transfer effort performance expectancy. LTSI questions are constructed using a Likert‐type scale ranging from 1 (Strongly Disagree) to 5 (Strongly Agree).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As co-teaching teams work together throughout a school year, the question that often arises is whether co-planning can be accomplished when common schedules and distractions of all types regularly occur (Carter et al, 2009; Santoli et al, 2008). Research has shown several ways in which co-teachers are making co-planning practical and effective within the normal constraints of their teaching schedules (Author, 2014; Blood, 2011; Brown et al, 2013; Conderman & Hedin, 2013; Dieker & Rodriguez, 2013; Leatherman, 2009; Murawski, 2012; Ploessl, Rock, Schoenfeld, & Blanks, 2010; Rice et al, 2007; Sayeski, 2009). Three general principles seen across the literature include (a) going beyond a typical school day to include online interactive solutions, (b) using the individual expertise of each educator, and (c) dividing and conquering so that each person does not have to do it all.…”
mentioning
confidence: 99%